EVALUATION OF ANTIOXIDANT AND ANTIMICROBIAL ACTIVITIES OF TARENNA ASIATICA (L.) O. KTZE. EX K. SCHUM. - KARTHIKKUMARAN, S.; SAJEESH, T.; PARIMELAZHAGAN, T.; VINODHKUMAR, V.; KAMALANATHAN, D.; NATARAJAN, T. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The study was aimed to analyze the phytochemical, antioxidant and antibacterial potentials of T. asiatica. Methods: The leaves, barks and flowers extracts were analyzed for total phenolic and flavonoid contents. Antioxidant activities were evaluated using DPPHâ— scavenging, ABTSâ—+ scavenging, FRAP, phosphomolybdenum reduction, metal chelating, nitric oxide radical scavenging, superoxide radical scavenging, hydroxyl radical scavenging and lipid peroxidation assays. Antibacterial activity was examined using agar well diffusion method against pathogenic microorganisms. Results: The total phenolic and flavonoid contents were found to be higher in acetone extract of leaves (57.21 g GAE/100 g and 619.67 mg RE/g respectively). Antioxidant assays revealed that leaves acetone extract possesses significant (p<0.05) DPPHâ— scavenging capacity (IC50: 20.38 Âµg/mL), ABTSâ—+ scavenging activity (10435.44 ÂµM TE/g), ferric reducing activity (152.13 mM Fe(II)E/mg), phosphomolybdenum reduction (417.93 mg AAE/g) and metal chelating activity (20.85 g EDTAE/100 g). At a concentration of 200 ug/mL, the leaves acetone extract also showed higher nitric oxide radical (49.22percent), superoxide radical (73.63percent) and hydroxyl radical (69.04percent) scavenging activities and inhibition for lipid peroxidation (57.38percent). Leaves and flowers acetone extracts inhibited the growth of S. dysenteriae, B. subtilis and S. boydii with an inhibition zone â‰¥12 mm. MIC of flowers acetone extract was found to be 20 Âµg/mL against both B. subtilis and S. boydii. Conclusion: T. asiatica contains considerable phenolic and flavonoid contents which is responsible for the evident antioxidant and antimicrobial activities. These findings validate that T. asiatica can be a natural antioxidant and antibacterial source which will address medical security. Keywords Antimicrobial, Antioxidant, Flavonoid, Free radical, Phenolic, Reactive oxygen species, Tarenna asiatica